Management of Fixed Asset Management at the Regional Finance Agency of Mataram City - Ramandani, Gilang; Suhaedi, Wirawan (Eduvest - Journal of Universal Studies, 2025)
This study focuses on the fixed asset management practices of Mataram City’s Regional Finance Agency, addressing the challenges and successes in managing regional assets in line with government regulations. The research aims to assess the efficiency of asset management processes, including planning, procurement, utilization, security, and maintenance, under the framework of Permendagri No. 47 of 2021. A descriptive qualitative method was applied, involving interviews, observations, and documentation from key informants, including officers from the Mataram City BKD. The results indicate that while asset management processes are generally aligned with the regulations, challenges such as input errors in bookkeeping, difficulties in determining asset values, and discrepancies between reported data and actual conditions persist. The study highlights the positive impact of Permendagri No. 47 of 2021 on asset management, though it also identifies areas for improvement, particularly in staff awareness and data accuracy. The findings suggest that enhanced training and further integration of digital tools are needed to optimize asset management practices in local governments. The implications of this research are valuable for policymakers, local governments, and asset managers, offering insights into improving asset management systems and ensuring financial transparency in regional administrations.